Laguncularia racemosa, White Mangrove - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
FOR 263, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this native evergreen tree that grows in the coastal areas of south Florida, the Caribbean, and Central America – scientific and common names, description, storm tolerance, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.